Perubahan Struktur Mikroanatomi Intestinum dan Hepar Ikan Mas (Cyprinus carpio) karena Pemberian Logam Berat Zn - Hirawati Muliani (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2006)
Heavy metal Zn comes into waters from paint and textile factories that have not adequately treated their waste. Small amount of Zn is necessary for metabolic activity of aquatic organisms, but it may cause toxicity when presents in abundance. This study was conducted to know differences between Zn effects on microanatomy structures of intestine and those on liver of Cyprinus carpio. The treatments arranged in a Completely Randomized Design (CRD) consisted of 0 ppm (control), 2 ppm, 4 ppm, and 6 ppm of Zn, which were applied respectively for 96 hours and replicated five times. The observed parameters were height of columnar epithellial cells of intestine and hepatocyte diameter. Data were analysed with F test followed by Least Significant Difference (LSD). The results showed that there was significant difference among treatments indicating that Zn affected microanatomy structures of intestine and liver of the fish.  Increase in height of columnar epithellial cells of intestine was recorded to begin at level of 4 ppm, while that in hepatocyte diameter was found to begin at level of 6 ppm.